جغرافيا الهجر الاستباقية بين مدخلات الفكر التوظيفي ومخرجات الفعل التأسيسي: دراسة في الجغرافيا التاريخية في الفترة من عام (1912) إلي عام (1932) - راشد، محمد عبدالقادر (جامعة الفيوم - كلية الآداب, 2022)
أضحى ما آلت إليه القوة السياسية للدولة ""العثمانية"" من ضعف وترد- واقعا ملموسا لدى العديد من الدول الأوروبية خلال العقدين الأول والثاني من القرن العشرين. ولقد أدى هذا الواقع إلى نوع من الفراغ السياسي اتضحت ملامحه في المنطقة النفيسة في الدولة ""العثمانية"" التي كانت تتمثل في المشرق العربي. وفي إطار هذه الواقعية وما ترتب عليها من فراغ سياسي تحولت منطقه ""المشرق العربي"" إلى فرصة تاريخية ذات أبعاد تفاوضية غير معلومة الاتجاه من ناحية، وذات أبعاد استعمارية تفكيكية من ناحية أخرى. وفي إطار هذا كله، وبجملة من الجغرافيات الاستباقية داخل الإطار العام للجغرافيات المضطربة في المشرق العربي آنذاك؛ كان ل ""عبد العزيز بن سعود"" مشروعه الخاص الذي بدأه منذ أن كان أميرا لمنطقه ""نجد"" في عام (1902 م) وتوج به ملكا على ""المملكة العربية السعودية"" في عام (١٩٣٦). ذلك المشروع العبقري الذي لو كتبت له الاستمرارية لشغل ""الفراغات السياسية"" كافة، في الدولة ""العثمانية"" آنذاك. فلقد انتهى إلى ""الهجرة"" بوصفها مجالا للتطبيق، فنبتت خطوة استقرار البدو وتوطينهم في قريتهم (الأولى) أو هجرتهم (الأولى) تحت أسم هجرة ""الأرطاوية"" في عام (١٩١٢). وبالنبت وبالهجرة (الأولى) نضج الفكر، فانتشرت ""الهجر"". ووفق الاتجاهات التوظيفية للهجر تكونت الأطر الثقافية للمعمور، فخلصت إلى جملة من الأحيزة الجغرافية القصدية، انتهت إلى جملة من الأحيزة الجغرافية الهجرية أظهرت فيما بينها درجات من التماسك الداخلي، فانتهى أمرها إلى تكوين الوحدة. وفي إطار هذا كله نشأ ""العمران التنموي"" من خلال إسقاط المنظومة المجتمعية/ الثقافية على الوسط البيئي أو الطبيعي؛ ذلك الإسقاط النشط الفعال الذي حدده فكر التغيير بالشكل الذي توافق مع مطالبه الملحة سعيا إلى الهدف المراد بلوغه. ومن ثم لم يكن ""العمران التنموي"" إلا نتاج فكر كان يؤمل من خلاله تحقيق غاية معينة ومرهونا بمجتمع معين، وبذلك يمكن عده مظهرا من مظاهر فعل المجتمع وفق فكر قاد عناصره الأساسية كافة إلى التضافر والتسابق؛ لتأمين الاستمرار الوظيفي للمجموع المتكامل. وعلى ضوء ذلك استمر العمران التنموي على مستوى ""المملكة العربية السعودية"" وتدافع لبلوغ اللامعلوم في ظل خطوات استباقية تارة أو بخطوات استشرافية تارة أخرى. وتدور فكرة الدراسة حول المدخلات التي أدت إلى تأسيس الهجر بعدها تجربة توظيفية انطوت على مجموعة من الآليات التنفيذية تم الاستدلال على نجاحها بمعلومية نتائجها التي توجت بتأسيس المملكة العربية السعودية في عام (١٩٣٢). وفي إطار ذلك استولدت فكرة دراسة ""الهجر"" كونها رؤية توظيفية بدافعية جملة من الغايات نجحت مخرجاتها بإدراك المزيد من الطموحات. ولقد اعتمدت الدراسة على المنهج التاريخي، في إطار محاولة بناء الأحداث التاريخية لقرى الهجر بعدها مجموعة من المحلات العمرانية اتصفت بمجوعة من الأبعاد السكانية، والعمرانية، والوظيفية بصفة عامة. كما اعتمدت على المنهج الاستدلالي الذي يعد بمنزلة الداعم الحيوي الذي أكسب الدراسة قوة الدفع للانتقال من حدث تاريخي إلى آخر كونه أتاح إمكانية الانتقال من المعرفة الجزئية الذاتية حيث خصائص ""الهجر"" إلى المعرفة الكلية حيث منطقه ""نجد"" ومن بعدها ""شبه الجزيرة العربية"" في رباط واحد. وبناء على ذلك أتاح المنهج الحكم على مدى دقة الحدث التاريخي وذلك بمقارنته، وربطه، واتساقه بالحدث الذي يليه. وبناء على خطوات المعالجة، فقد شملت الدراسة (ستة) محاور رئيسة غلب عليها الاتجاه الأصولي في إطار من التحليل والنقد، أما الاتجاه الانتفاعي فلقد تمثل في نتائج الدراسة وتوصياتها." The weakness and decline of the political power of the "Ottoman" Empire became a tangible reality for many European countries during the first and second decades of the twentieth century. This reality led to a kind of political vacuum whose features became evident in the precious region of the "Ottoman" Empire, which was represented in the Arab Mashriq. In the context of this realism and the consequent political vacuum, the "Arab Mashriq" region has become a historic opportunity with a negotiating dimension of unknown direction, on the one hand, and a deconstructive colonial dimension, on the other. Within the framework of all this, and with a set of proactive geographies within the general framework of turbulent geographies in the Arab Mashriq at that time; "Abdul Aziz bin Saud" had his own project, which he started since he was the Prince of the "Najd" region in the year (1902 AD) and he was crowned king of the "Kingdom of Saudi Arabia" in the year (1936). That genius project that, if it was to continue, would occupy the entire "political vacuums" in the "Ottoman" Empire at the time. It ended with "migratory" as a field of application, so the step of settling and settling the Bedouins in their (first) village or their (first) migration under the name of "Al-Artawiya" migration took place in 1912. Because of the (first) migration, the thought matured, and the “migratory” spread. According to the staffing trends of emigration, the cultural frameworks of the globe were formed, which showed among themselves degrees of internal cohesion, which led to the formation of unity. Within the framework of all this, "developmental urbanism" has been arisen by projecting the comnuinity/ cultural system onto the environmental or natural milieu; That active, effective projection defined by the thought of change in a manner consistent with its pressing demands in pursuit of the goal to be achieved. Hence, "developmental urbanism" was only the product of a thought through which it was hoped that a specific goal would be achieved and dependent on a particular society. Thus, it can be considered as a manifestation of the society's action according to a thought that led all its basic elements to unite and compete to secure the functional continuity of the integrated group. In light of this, the developmental urbanism has continued in the Kingdom of Saudi Arabia and has been advocated to reach the unknown in light of proactive steps at times or by forward- looking steps at other times. The idea of the study revolves around the inputs that led to the establishment of migratory as a staffing experience that involved a set of executive mechanisms, whose success was demonstrated by the knowledge of its results, which culminated in the establishment of the Kingdom of Saudi Arabia in (1932). The study relied on the historical method, in the context of an attempt to build the historical events of the villages of migratory as a group of urban places characterized by a set of demographic, urban, and staffing dimensions in general. The study also relied on the evidentiary approach, which is considered as the vital support that gave the study the impetus to move from one historical event to another. The evidentiary approach has made it possible to move from the subjective partial knowledge where the characteristics of "migratory" are, to the total knowledge, where the "Najd" region and then "the Arabian Peninsula" are in one bond. Based on that, the approach made it possible to judge the accuracy of the historical event by comparing it, linking it, and its consistency with the next event. Because of the processing steps, the study included (Six) major points, which were dominated by the fundamentalist trend within a framework of analysis and criticism. As for the utilitarian part, it was represented in the results and recommendations of the study.
Keywords: الافكار التوظيفية -- الجغرافيا التاريخية -- جغرافيا الهجر -- الهجرة الأرطاوية